A comparative morphological and histological study of the female reproductive organs of Psycharium montanum (Megalopygidae) and Neurosymploca sp. US 1 (Zygaenidae) (Lepidoptera) - Pretorius, Etheresia (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.